THE CONCEPT AND PRINCIPLES OF PUBLIC ADMINISTRATION IN THE FIELD OF TOURISM (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This scientific article talks about the effectiveness of mechanisms of implementation in the tourism activity in our country, the role of this industry in the concept and principles of state management.